Diversity and ethnomycological importance of mushrooms from Western Himalayas, Kashmir - Tariq Saiff Ullah; Syeda Sadiqa Firdous; Wayne Thomas Shier; Javeed Hussain; Hamayun Shaheen; Muhammad Usman; Maryam Akram; Abdul Nasir Khalid (BMC, 2022)
Abstract Background Wild edible mushrooms (WEM) are economically significant and used in traditional medicines worldwide. The region of Jammu and Kashmir (Western Himalayas) is enriched with the diversity of edible mushrooms, collected by the rural people for food and income generation. This is the first detailed study on diversity and ethno-medicinal uses of mushrooms from the State of Jammu and Kashmir. Methods Consecutive surveys were conducted to record ethnomycological diversity and socio-economic importance of wild edible mushrooms value chain in rural areas of Azad Jammu and Kashmir during 2015-2019. Ethnomycological data were collected with a semi-structured questionnaire having a set of questions on indigenous mycological knowledge and collection and retailing of wild edible mushrooms. A total of 923 informants from the study area provided the results identifying the gender, type of mushroom species, medicinal uses, and marketing of mushrooms. Diversity of mushrooms was studied by using quadrat and transect methods. Principal component analysis (PCA) and detrended correspondence analysis (DCA) were also applied to the dataset to analyse the relationship between species distribution, the underlying environmental factors, and habitat types. PCA identified the major species-specific to the sites and put them close to the sites of distribution. Results A total of 131 mushroom species were collected and identified during 2015-2019 from the study area. Ninety-seven species of mushrooms were reported new to the State of Azad Jammu and Kashmir. The dominant mushroom family was Russulaceae with 23 species followed by Agaricaceae, 16 species. Major mushroom species identified and grouped by the PCA were Coprinus comatus, Lactarius sanguifluus, Amanita fulva, Armillaria gallica, Lycoperdon perlatum, Lycoperdon pyriforme, and Russula creminicolor. Sparassis crispa, Pleurotus sp, and Laetiporus sulphureus were recorded most edible and medicinally significant fungi. Morels were also expensive and medicinally important among all harvested macro-fungal species. These were reported to use against common ailments and various health problems. Conclusions Collection and retailing of WEM contribute to improving the socio-economic status, providing alternative employment and food security to rural people of the area. These mushrooms are used as a source of food and traditional medicines among the rural informants and could be used as a potential source of antibacterial and anticancer drugs in the future.